Role of transcutaneous electrical nerve stimulation in temporomandibular joint disorders - Syeda Mahnoor Fatima; Tooba Zahoor; Ramsha Nawaz; Ahmed Tanveer; Syeda Soveba Zaidi; admin (Journal of the Pakistan Medical Association)
Objective: To compare the efficacy of transcutaneous electrical nerve stimulation with commercially available analgesics in alleviating symptoms of temporomandibular disorders.